Effect of convalescent plasma on organ support-free days in critically ill patients With COVID-19: a randomized clinical trial - Estcourt, LJ; Turgeon, AF; McQuilten, ZK; McVerry, BJ; Al-Beidh, F; Annane, D; Arabi, YM; Arnold, DM; Beane, A; Bégin, P; van Bentum-Puijk, W; Berry, LR; et al. (American Medical Association, 2021)
Importance: The evidence for benefit of convalescent plasma for critically ill patients with COVID-19 is inconclusive.